Thermal condition of cohesion in a two-layer roll of a rolling mill - Demyanchenko, Olga Panteleivna; Lyashenko, Viktor (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2019)
A condition of heat exchange between the layers having different thermalphysic properties in a two-layer cylindrical roll of a rolling mill is analyzed foe an ideal thermal contact. It can be realized with application of the condition of heat balance of one of the layers in the cylindrical area for a homogeneous equation of heat conductivity. Analyzed was a simplified target setting in the radial section with a supposition, regarding an averaged in radius temperature distribution in the outer layer. By applying the condition of the thermal balance and by integrating the homogeneous equation of heat conductivity in the two-layer area a condition of cohesion of an impedance type in case of an ideal thermal contact between the layers was constructed.